'Children in good order' : a study of constructions of child protection work of the Royal Scottish Society for the Prevention of Cruelty to Children, in the West of Scotland, 1960-1989 - Robinson, Anna Christina Mary (2002)
How did the Royal Scottish Society for the Prevention of Cruelty to Children protect children in post war Glasgow? The analysis in this study of the 'construction' of child protection is centred upon three questions relating to the practice of the RSSPCC: What forms did intervention take? Who was the focus of practice? How and why did practice change during the 30 year period, 1960-1990, of this study? The period 1960-1990 witnessed rapid political, economic and social changes which contributed to the recognition by the state of social problems which affected families. The RSSPCC (founded in 1884) was established by the beginning of the twentieth century as the principal arm of the state in the investigation and prosecution of child abuse and neglect throughout Scotland. The Society sustained this key role up to the middle of the 1970s and then lost it completely in 1992. This study is not a history of the RSSPCC. However an historical perspective was adopted to further understanding of the organisation's role in Scottish society and in the lives of families whose standards of parenting were causing concern. The sources of that concern were found often within the family. Many mothers (less often fathers) sought assistance from the RSSPCC only to find themselves subjects of intense scrutiny and intervention. The analysis and conclusions of this study are derived from: the RSSPCC case records of intervention in the lives of 1,500 families, the records of 120 prosecutions of parents for cruelty and or neglect, a selection of Annual Reports from 1889 to 1993, and interviews with 51 RSSPCC staff. A theoretical framework which brought historical sociology, post structuralist models of power and feminism together with the concept of 'Adocentrism' (the unswerving allegiance to adult values) was developed to illuminate the puzzles, paradoxes and complexities of the changing constructions of child protection. This study concludes that the 'construction' of child protection developed and changed in response to a number of factors. However, the power to define and negotiate the subjects and boundaries of intervention was invariably retained by the professionals and furthermore the focus of that intervention was predominantly with and between adults